2022
DOI: 10.3390/ijerph192416748
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Influence of Mandibular Flexure on Oral Rehabilitation: Narrative Review

Abstract: Aim: The current paper aims to review mandibular flexure and its clinical implications in the field of oral rehabilitation. Mandibular flexure is a deformity of the mandible, which occurs during jaw movements. Methods and Materials: An electronic database search was conducted using the PRISM model, with a total of 49 articles included. Results: Mandibular flexure affects various stages of oral rehabilitation treatments. Effects of mandibular flexure are more significant in periodontal patients, and in implant-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 40 publications
0
11
0
1
Order By: Relevance
“…A recent review concluded that mandibular flexure might be more pronounced in periodontal patients and implant-supported restorations, compared to natural teeth, due to differences in the forces absorbed by the periodontal apparatus. The authors suggested that for implant-retained restorations, it is advisable to split the prosthesis into two or three components [ 31 ]. This may prevent the major porcelain fracture immediately after prosthesis insertion.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review concluded that mandibular flexure might be more pronounced in periodontal patients and implant-supported restorations, compared to natural teeth, due to differences in the forces absorbed by the periodontal apparatus. The authors suggested that for implant-retained restorations, it is advisable to split the prosthesis into two or three components [ 31 ]. This may prevent the major porcelain fracture immediately after prosthesis insertion.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 Another factor that is worth of consideration in terms of implant prosthetic success was the sliding bar, able to anchor the overdenture and to follow the mandibular transverse growth or bone deformation during chewing or mouth opening and closure. [33][34][35] Our decision to proceed with a sliding bar was based on the fact that the mandible was extremely thin in these patients and possibly subjected to deformation during functioning. 34 In addition, this bar, by sliding instead of rigidly blocking the implants, avoids any horizontal interferences with the mandible growth.…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35] Our decision to proceed with a sliding bar was based on the fact that the mandible was extremely thin in these patients and possibly subjected to deformation during functioning. 34 In addition, this bar, by sliding instead of rigidly blocking the implants, avoids any horizontal interferences with the mandible growth. Furthermore, the possibility of each half of the bar to have a rotation on the OT Equator attachment gives more degree of freedom to the prosthesis itself that could be important in young patients.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, in order to minimise deformation when taking traditional impressions for the lower jaw, it has been suggested that impressions should be made with a minimum mouth opening, as close to the upper jaw as possible and ideally with no more than 20 mm, so as to involve minimal activation of the masticatory muscles [ 15 ]. In addition, any protrusive movement should be avoided and, while hardening the impression, the dentist should avoid touching the patient’s jaw, pushing it up or down [ 41 ]. The extent of minimisation is uncertain, however, given the limited literature on the subject.…”
Section: Discussionmentioning
confidence: 99%